Phytochemicals and Antioxidant Potential of Amaranthus spinosus Seed Extracts - Hanan Abdul Qader Abdulilah (Academia Open, 2025)
General Background: Amaranthus spinosus, a member of the Amaranthaceae family, has long been valued in culinary and medicinal traditions due to its diverse bioactive compounds. Specific Background: Previous studies have highlighted its phenolic content and antioxidant potential, yet limited research has compared solvent efficiency in extracting these compounds. Knowledge Gap: The influence of solvent polarity on phytochemical diversity and antioxidant activity of A. spinosus seeds remains underexplored. Aims: This study aimed to investigate the phytochemical composition and antioxidant capacity of aqueous and alcoholic extracts of A. spinosus seeds. Results: Both extracts contained polyphenols, flavonoids, terpenoids, alkaloids, and saponins, though glycosides were exclusive to the aqueous extract, while carotenoids and cardiac glycosides were unique to the alcoholic extract. Antioxidant assays revealed stronger radical scavenging activity in the alcoholic extract (88%) than in the aqueous extract (75%), though both were below the ascorbic acid standard. Novelty: By demonstrating solvent-specific extraction patterns, this study underscores alcohol as a superior medium for isolating antioxidant constituents in A. spinosus seeds. Implications: These findings validate the traditional use of A. spinosus and suggest its potential application as a natural antioxidant in pharmaceutical and food industries Highlights: Alcoholic extract showed higher antioxidant capacity (88%) than aqueous (75%). Solvent choice influenced phytochemical diversity and yield. Supports traditional medicinal use and potential food/pharma applications. Keywords: Amaranthus spinosus, Phytochemicals, Antioxidant Activity, Solvent Extraction, Bioactive Compounds